The 1909 Lviv Church Exhibition in the context of the exhibitions of Polish church art and religious art and the production of liturgical objects at the turn of the 20th century - Kaliszuk, Magdalena (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The Liturgical Industry Exhibition “including building and interior decoration of Roman Catholic and Orthodox churches as well as Isr[aeli] prayer houses”, known also as the Church Exhibition, was one of the first and biggest exhibitions of the Polish liturgical industry. Its organizers, the Industrial Aid League, adopted the formula of national exhibitions, popular in Europe, whose aim was to showcase the cultural, scientific and technological achievements of a given country and region, as well as to encourage local industrialists to fight against foreign competition. The aim of the exhibition was to open up to different cultures and religions. Works of art and consumer goods related to the Latin, Greek-Catholic, Armenian and Judaic religions were presented by over 120 exhibitors, mainly from the Austrian partition. The exhibition was accompanied by a brochure “The Catalogue of the Church Exhibition”, which was sent to the parishes and municipalities of Galicia and on request to interested persons.

Wystawa Przemysłu Liturgicznego „z zakresu budowy i wewnętrznego urządzenia kościołow, cerkwi i izr[aelskich] domow modlitwy”, zwana Wystawą Kościelną, była jedną z pierwszych i jedną z większych wystaw polskiego przemysłu liturgicznego. Organizując ją, Liga Pomocy Przemysłowej przyjęła popularną w Europie formułę wystaw krajowych, ktorych celem było ukazanie dorobku kulturalnego, naukowego, technicznego danego kraju, regionu oraz zachęcenie lokalnych przemysłowcow do walki z obcą konkurencją. Założeniem programowym wystawy było otwarcie na rożne kultury i religie. Dzieła sztuki i wyroby przemysłowe związane z wyznaniami: łacińskim, greckokatolickim, ormiańskim i judaistycznym zaprezentowało blisko 120 wystawcow, głownie z zaboru austriackiego. Wystawie towarzyszył broszurowy „Katalog Wystawy Kościelnej”, ktory rozsyłano do parafii i gmin galicyjskich oraz na zamowienie zainteresowanym osobom.
Wystawa Kościelna we Lwowie w 1909 roku w kontekście wystaw polskiej sztuki kościelnej i religijnej oraz przemysłu liturgicznego na początku XX wieku
Translated by Monika Mazurek.
Keywords: The Lviv Church Exhibition; the Liturgical Industry Exhibition; Lviv; church art; religious art; liturgical industry; church industry; the Industrial Aid League; devotional products; Wystawa Kościelna we Lwowie; Wystawa Przemysłu Liturgicznego; Lwów; sztuka kościelna; sztuka religijna; przemysł liturgiczny; przemysł kościelny; Liga Pomocy Przemysłowej; wyroby dewocyjne